Deformation of single and multiple laser peened TC6 titanium alloy. (1st March 2018) - Umapathi, A.; Swaroop, S.
Highlights: Laser peening without coating done on TC6 (variable power densities and multiple peening). Softening (of α phase) noticed after 6 GW cm −2 (single peening) and 3 passes (multiple peening). α to β phase transformation accompanied softening, confirmed by synchrotron radiation and microscopy. Abstract: Laser peening without coating (LPwC) was done on the titanium TC6 alloy at a wavelength of 532 nm using an Nd:YAG laser. The laser power densities of 3, 6 and 9 GW cm −2 were used to peen the samples. Samples were also peened multiple times (1, 3 and 5 passes) at 6 GW cm −2 . Microhardness showed an overall 23% increase from the baseline value. Further, softening of α phase in the bulk was observed above 6 GW cm −2 in the samples peened once and above 1 pass in multiply peened samples. A similar trend was observed from the residual stress analysis of the samples. The maximum compressive residual stress was −1780 MPa at a depth of 50 μm at 9 GW cm −2 . The observed softening of α phase was proposed due to adiabatic heating. Microstructural changes due to adiabatic heating resulting in increased β volume fractions were observed and confirmed by synchrotron radiation measurements.